Skin Erosion and Exteriorisation of a Cardiac Implantable Electronic Device: Modified Surgical Approach - Sazzad, Faizus; Ibrahim, Farzana B; Khan, Md Saidur Rahman (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Skin erosion and exteriorization of the commonest cardiac implantable electronic device (CIED) is usually caused by localized infection as a result of “pocket” infection. But, there are other recognized factors including an advanced age with thin, fragile skin with precarious subcutaneous fat. So, exteriorisation of a generator, and/or a lead, is not always associated with bacterial contamination followed by antibiotic therapy and contra-lateral re-implantation strategy. Hence, it does not always make the removal of the material an obligation. Our notable findings in a rare case of such exteriorization stimulate us to look for and implement a modified surgical technique. This 93-year-old extremely aged wonderfully co-operative, multi-morbid woman had multiple episodes of skin erosion and fixation, re-fixation surgery till the best result achieved. We present a new technique for cardiac pacing allowing for full patient recovery via an alternative surgical way of CIED relocation. J Bangladesh Coll Phys Surg 2020; 38(3): 155-157